SCP2-mediated cholesterol membrane trafficking promotes the growth of pituitary adenomas via Hedgehog signaling activation - Ding, Xiao (J Exp Clin Cancer Res, 2019)
BACKGROUND: Metabolic reprogramming is an important characteristic of tumors. In the progression of pituitary adenomas (PA), abnormal glucose metabolism has been confirmed by us before. However, whether cholesterol metabolism is involved in the process of PA remains unclear. This study aimed to investigate whether abnormal cholesterol metabolism could affect the progression of PA. METHODS: We analyzed the expression of sterol carrier protein 2 (SCP2) in 40 surgical PA samples. In vitro experiments and xenograft models were used to assess the effects of SCP2 and cholesterol on proliferation of PA. The incidence of hypercholesterolemia between 140 PA patients and 100 heathy controls were compared. RESULTS: We found an upregulation of SCP2 in PA samples, especially in tumors with high proliferation index. Forced expression of SCP2 promoted PA cell lines proliferation in vitro. Furthermore, SCP2 regulated cholesterol trafficking from cytoplasm to membrane in GH3 cells, and extracellularly treating GH3 cells and primary PA cells with methyl-β-cyclodextrin/cholesterol complex to mimic membrane cholesterol concentration enhanced cell proliferation, which suggested a proliferative effect of cholesterol. Mechanistically, cholesterol induced activation of PKA/SUFU/GLI1 signaling via smoothened receptor, which was well-known as Hedgehog signaling, resulting in inhibiting apoptosis and promoting cell cycle. Accordingly, activation of Hedgehog signaling was also confirmed in primary PA cells and surgical PA samples. In vivo, SCP2 overexpression and high cholesterol diet could promote tumor growth. Intriguingly, the incidence of hypercholesterolemia was significantly higher in PA patients than healthy controls. CONCLUSIONS: Our data indicated that dysregulated cholesterol metabolism could promote PA growth by activating Hedgehog signaling, supporting a potential tumorigenic role of cholesterol metabolism in PA progression.